2019
DOI: 10.1111/ppa.13085
|View full text |Cite
|
Sign up to set email alerts
|

Automated image processing framework for analysis of the density of fruiting bodies of Leptosphaeria maculans on oilseed rape stems

Abstract: Understanding the transmission of plant pathogen inoculum during the periods when the host plants are not present is crucial for predicting the initiation of epidemics and optimizing mitigation strategies. However, inoculum production at the end of the cropping season, survival during the intercrop period, and the emergence or release of inoculum can be highly variable, difficult to assess, and generally inferred indirectly from symptom data. As a result, a lack of large datasets hampers the study of these epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Further, by keeping track of individual stem severity and comparing a susceptible cultivar with one having quantitative resistance, Lô-Pelzer et al (2009) were able to see the effect of a genotype with quantitative resistance on the distributions of severities, though they observed no effect of the genotype at a given severity. Afterwards, it has been shown that the production of fruiting bodies on incubated stems can be significantly impacted by the field where they were collected (Bousset et al, 2019). However, this study did not allow distinguishing between the effects of genotype and cropping practices.…”
Section: Fig 1 Schematic Representation Of Cyclic Epidemics and Thementioning
confidence: 97%
See 4 more Smart Citations
“…Further, by keeping track of individual stem severity and comparing a susceptible cultivar with one having quantitative resistance, Lô-Pelzer et al (2009) were able to see the effect of a genotype with quantitative resistance on the distributions of severities, though they observed no effect of the genotype at a given severity. Afterwards, it has been shown that the production of fruiting bodies on incubated stems can be significantly impacted by the field where they were collected (Bousset et al, 2019). However, this study did not allow distinguishing between the effects of genotype and cropping practices.…”
Section: Fig 1 Schematic Representation Of Cyclic Epidemics and Thementioning
confidence: 97%
“…For instance, imaging and existing processing algorithms to segment and count regions, offers the prospect to circumvent the long and tedious manual counting (Stewart et al, 2016;Karisto et al, 2018;Yang & Hong, 2018). In the particular case of L. maculans, the automated quantification of fruiting bodies through image processing have already been tackled (Bousset et al, 2019), offering a means to overcome the experimental bottleneck and assessing the effect of host quantitative resistance on pathogen carry-over.…”
Section: Fig 1 Schematic Representation Of Cyclic Epidemics and Thementioning
confidence: 99%
See 3 more Smart Citations